Financial Linkages Across Korean Banks - Aydin, Burcu (IMF Working Papers; Working Paper ;, 2011)
This paper assesses the interconnectedness across Korean banks using three alternative methodologies. Two methodologies utilize high frequency financial data while the third uses bank balance sheet data to assess banks' bilateral exposures, systemically vulnerable banks, and systemically risky banks. The analysis concludes that while Korean banks are interconnected, both the financial risk and contagion risk from such interconnectedness have declined significantly in the aftermath of the global financial crisis.